복음주의 선교신학 관점에서 선교로서의 비즈니스선교 개념에 대한 선교신학적 근거 고찰 - 로잔운동 공식문서를 중심으로 - 김광성(KIM Kwang-Seong) (Changsin nondan, 2019)
선교학은 독립된 학문으로서 다양한 주제에 대한 이론화 작업을 하고 있다. 통전적 선교 개념이 등장하면서 NGO, 디아스포라, 이주민, 비즈니스 등이 선교 신학의 중요한 연구 분야가 되었다. 비즈니스는 21세기 선교 실천에서 중요한 수단이 될 것이다. 그런데 한국 교회가 비즈니스를 선교실천 영역으로 적극적으로 수용하지 못하는 것은 비즈니스 선교신학 이론에 대한 이해가 부족하기 때문이다. 본 연구는 선교로서의 비즈니스 선교신학의 이론적 근거를 제시하여 비즈니스 선교실천 영역에서 있는 사역자들이 신학적 갈등 없이 사역할 수 있게 되기를 기대 한다. 선교로서의 비즈니스 개념은 로잔운동을 통해 선교신학 이론으로 발전한다. 세 차례 로잔대회에서 발표한 <로잔언약>, <마닐라선언>, <케이프타운서약>은 선교로서의 비즈니스 개념이 복음주의 진영의 선교신학으로 자리 잡는데 중요한 역할을 하였다. <로잔언약>에서는 전도와 사회참여를 모두 선교의 영역으로 선언으 로써 비즈니스가 선교실천 영역임을 인정하는 계기가 되었다. <마닐라선언>에서는 성직주의에 대한 경고를 바탕으로 비즈니스 현장의 주체인 비즈니스 전문가의 선교실천적 역할이 강조된다. <케이프타운서약>에서는 일터를 선교실천 현장으로 규정함으로써 선교로서의 비즈니스 개념이 선교신학 이론으로 자리 잡게 되었다. 이처럼 선교로서의 비즈니스는 토착화 선교, 하나님의 선교 개념, 상황화 신학, 총체적 선교로 이어지는 현대 선교신학의 발전과정과 로잔운동의 선교신학 정립을 통해 선교신학의 중요한 이론이 되었다. Missiology, as an independent discipline, is working on theorizing various subjects. With the advent of the Holistic Mission, NGO, Diaspora, Migrant, and Businesses have become important research areas in Missiology. The business will be an important tool in the practice of missionary work in the 21st century. However, the reason why Korean churches cannot actively embrace business as a field of missionary practice is that they lack an understanding of BAM. I hope that this study will present the theoretical basis of BAM so that the missionaries in the field of business missions can serve without theological conflict. The concept of BAM develops into the theory of missiology through the Lausanne movement. The Lausanne Covenant, the Manila Manifesto and the Cape Town Commitment played an important role in establishing the concept of BAM in the evangelical camp. In the Lausanne Covenant, both evangelism and social participation were declared as areas of Mission, thereby giving rise to the recognition of the BAM practice. The Manila Manifesto emphasizes the missionary role of a businessman, who is the main player in the business scene, based on his warning of clericalism. In the Cape Town Commitment, the concept of BAM became the theory of missiology by defining the workplace as the site of mission practice. As such, BAM became an important theory of missiology through the development of modern missiology and the establishment of missiology of the Lausanne movement, leading to a Holistic mission, the concept of Missio Dei, the contextualization, and the Holistic mission. KCI Citation Count: 8